Best Answer

If by 3 0 you mean 3º: Any number, except 0, to the 0 power equals 1.

For example: 1 = 9/9 = 3²/3² = 3²-² = 3º = 1

To divide 3² by 3², subtract exponents.

By extension xª/xª = xº = 1, x <> 0

"<>" signifies "is not equal to" since it means "is less than or greater than" and therefore not equal to

🙏

🤨

😮

Q: Why is 3 0 equal to 1 and what is the reason?

Write your answer...

Submit

Related questions

The answer is 0. For example, 1/3 - 1/3 = 0/3 which is equal to 0.

3ab0*0*1*3*3a = 0

Anything with a zero in the numerator will be equal to 0. If your problem is 0/1/3, then it's 0.

0=0 in binary 1=1 2=10 3=11 . . . Got it?

Minus 1 times 0 plus 3 divided by 3 is equal to 1

0 over 3 is equal to 0.

The integers less than or equal to 2 are: {2, 1, 0, -1, -2, -3, ...}

If you mean: (3x-1)(x+1) = 0, then it is 3x squared+2x-1 = 0. Its solutions are: x = 1/3 or x = -1.

0

if you look on at this. 3^2=9 3^1=3 3^0=1 it's dividing by 3 every time so the answer for 3^0 =1

The numbers are -3, -2, -1, 0 and 1. Also, -5, -3, -1, 1 and 3.

grapes

3 to the exponent of 0 is 1. In fact, any non-zero number, raised to the power of 0 is equal to 1.

anything to the power of 0, always equals 1. This is what i know. Hope I answered your question.

No. It is 3 less than 0.

{-1, 0, 1} {-2, -1, 0, 1, 2} {-3, -2, -1, 0, 1, 2, 3} and so on form one family of such numbers.

Anything to the power of 0 is 1 (except 0 for some strange reason), so yes.(a+b)0= 1 3(a+b)0= 3 (3a+3b)0= 1

1+4 2+3 3+2 4+1 5+0

Here are 4 examples: 2x1 , 1x2 , 2+0 , 0+2 , 3 -1 , etc.

A Pentagon has 5 angles. It can have 0, 1, 2, 3 or all 5 equal.

3/5 is closest to 1/2. Reasoning: 3/5 is equal to 0.6, which is closest to 0.5 (or 1/2) NOT 0, or 1.

0+5, 1+4, 2+3, 1x5

An algebraic expression that is not equal (Such as 3=0) is called an inequality, and can be expressed as 3≠0.

A huge number. 0 + 1 + 2 = 3 0 + 2 + 1 = 3 1 + 0 + 2 = 3 1 + 2 + 0 = 3 2 + 0 + 1 = 3 2 + 1 + 0 = 3 -0 + 1 + 2 = 3 -0 + 2 + 1 = 3 1 - 0 + 2 = 31 + 2 - 0 = 32 - 0 + 1 = 32 + 1 - 0 = 3 0 - 1 + 3 = 2 0 + 3 - 1 = 2 -1 + 0 + 3 = 2 -1 + 3 + 0 = 2 3 + 0 - 1 = 2 3 - 1 + 0 = 2 -0 - 1 + 3 = 2-0 + 3 - 1 = 2-1 - 0 + 3 = 2-1 + 3 - 0 = 23 - 0 - 1 = 23 - 1 - 0 = 2 0 - 2 + 3 = 1 0 + 3 - 2 = 1 -2 + 0 + 3 = 1 -2 + 3 + 0 = 1 3 + 0 - 2 = 1 3 - 2 + 0 = 1 -0 - 2 + 3 = 1-0 + 3 - 2 = 1-2 - 0 + 3 = 1-2 + 3 - 0 = 13 - 0 - 2 = 13 - 2 - 0 = 1 1 + 2 - 3 = 0 1 - 3 + 2 = 0 2 + 1 - 3 = 0 2 - 3 + 1 = 0 -3 + 1 + 2 = 0 -3 + 2 + 1 = 0 For each of these equations there is a counterpart in which all signs have been switched. For example 0 + 1 + 2 = 3 gives -0 - 1 - 2 = -3and so on. Now, all of the above equations has three numbers on the left and one on the right. Each can be converted to others with two numbers on each side. For example:the equation 0 + 1 + 2 = 3 gives rise to0 + 1 = 3 - 20 + 1 = -2 + 30 + 2 = 3 - 10 + 2 = -1 + 31 + 2 = 3 - 01 + 2 = -0 + 3-0 + 1 = 3 - 2-0 + 1 = -2 + 3-0 + 2 = 3 - 1-0 + 2 = -1 + 31 + 2 = 3 + 01 + 2 = +0 + 3 As you can see, the number of equations is huge!

2 x 2 + x - 1 = 0 4 + x - 1 = 0 4-1 + x = 0 3 + x = 0 3 + x - 3 = 0 - 3 x = -3 ---------- Another Solution Method (including text) for: 2 * 2 + x - 1 = 0 1. Do simple operations (*/+-) within from left to right: 2 * 2 + x - 1 = 0 4 + x - 1 = 0 3 + x = 0 2. Group like terms: - move numerical terms from the left side of the equal sign to the right side of the equal sign (remember to change the sign when moving from the left to the right of the equal sign): 3 + x = 0 x = 0 - 3 3. Do simple operations (^*/+-): x = 0 - 3 x = - 3

Study guides